The Role of Management Ownership in Moderating the Effect of Company Size, Profitability, and Leverage on Company Value - Viandika, Adhimsyah Huda; Tjahjono, Achmad (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Competition between companies encourages managers to formulate strategies and make important decisions to ensure the survival of the company and achieve its established goals. This study aims to utilize managerial ownership as a moderating variable to analyze the effect of company size, profitability, and leverage on company value. The research objects include companies listed on the LQ45 index of the Indonesia Stock Exchange (IDX) during the period 2019–2023. Using secondary data from annual financial reports, this study employs a quantitative approach. The data analysis method used is multiple linear regressions, which tests the direct relationship between the dependent variable (company value) and the independent variables (company size, profitability, and leverage). Additionally, this study examines the role of managerial ownership in moderating the relationship between these variables. The results indicate that company size, profitability, and leverage significantly affect company value. Specifically, company value increases with optimal management of size, profitability, and leverage. Furthermore, managerial ownership strengthens the relationship between these independent variables and company value.